Degradação da interface aço-pasta de cimento de poços de injeção de CO2 para armazenamento geológico em aquífero salino da Bacia do Paraná - Dalla Vecchia, Felipe (2012)
The emission of greenhouse gases to the environment can be reduced by the adoption of the technology of geological storage of carbon. However, the materials usually employed in the construction of CO2 injection wells do not resist the acid attack by the CO2 in the presence of brine and suffer degradation in longer exposure times. Field and laboratory studies indicate that degradation of the materials occurs mainly at the interface between the cement paste and the steel casing. In this work, experiments that simulate the conditions of CO2 storage in saline aquifers of the Paraná Basin at a depth of 1500 m were conducted to investigate the chemical integrity of Class G cement paste and API N80 steel, involving a failure at interface steel-cement paste in different times (48h, 380h and 720h). The degradation of the cement paste was evaluated in terms of characteristics and depth of the region chemically modified. The corrosion films formed on steel were characterized in terms of morphology and thickness. The influence of these films on the steel corrosion resistance was evaluated by electrochemical measurements of open circuit potential and potentiodynamic polarization. The results indicate that the degradation or corrosion processes depend on the media that the system steel- cement paste was submitted and the exposure time. The degradation of the cement paste involved the formation of two zones, carbonated zone of high density and bicarbonate zone of high porosity, and the latter zone is critical since it can provide a path to CO2 leakage. The films of corrosion product formed on the steel are composed by iron-calcium complex carbonates and they have protective characteristics to the steel casing considering the experimental conditions used in this work.